The Relationship Between Pre-Pregnancy Body Mass Index (BMI) and Weight Gain During Pregnancy with the Incidence of Stunting in Toddlers in the Working area of Pekauman Health Center - Claudia, Jesika; Ariani, Malisa; Latifah, Latifah (PROMOTOR, 2025)
Stunting is a chronic nutritional problem caused by long-term inadequate nutritional intake, resulting in impaired growth in children. The nutritional status of pregnant women can be measured through body mass index (BMI) and weight gain during pregnancy, which reflect the nutritional condition of the mother and fetus. This study aims to determine the relationship between pre-pregnancy BMI and weight gain during pregnancy with the incidence of stunting in toddlers in the working area of Pekauman Health Center. This research uses a quantitative method with a Cross-Sectional approach, involving 30 respondents selected through purposive sampling. Data were collected using mother and child observation sheets and the KIA book, then analyzed using the Kolmogorov-Smirnov and Chi-Square tests. The results showed no significant relationship between pre-pregnancy BMI and the incidence of stunting, but there was a significant relationship between weight gain during pregnancy and the incidence of stunting in toddlers.